2019
DOI: 10.12911/22998993/102841
|View full text |Cite
|
Sign up to set email alerts
|

Cleaning of Effluents from Ions of Heavy Metals as Display of Environmentally Responsible Activity of Modern Businessman

Abstract: This work is dedicated to the development of scientific technologies of sewage water clarification of different industrial enterprises from chrome and nickel ions through adsorption by bentonite from Cherkasy field under dynamic conditions. The perspective and efficiency of application of bentonite clays for treatment of sewage water are confirmed by their advantages over other sorbents, that is: they win in accessibility, cost, and possibility of regeneration and multiple usages. The studies proved the expedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…The issue of reducing the microbial count under the action of cavitation is also debatable. The authors [15,16] indicate the selectivity of zeolites for organic acids. There are data in the literature on the use of adsorption methods for wastewater treatment of dairy enterprises [9,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The issue of reducing the microbial count under the action of cavitation is also debatable. The authors [15,16] indicate the selectivity of zeolites for organic acids. There are data in the literature on the use of adsorption methods for wastewater treatment of dairy enterprises [9,12].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that zeolites have the ability to adsorb ions not only by the mechanism of physical adsorption, but also by the mechanism of ion exchange and manifest themselves as ion exchangers. The literature describes the sorption processes, gives the isotherms of adsorption of various substances on zeolites and other aluminosilicates [15,16]. In our previous works, we reported that α-oxypropionic acid is well adsorbed by zeolite [17].…”
Section: Introductionmentioning
confidence: 99%
“…Real-time monitoring of air pollution [Chugai et al, 2020] and surface watercourses [Odnorih et al, 2020;Sakalova et al, 2019] and scientifically grounded analysis of the data of this monitoring is a prerequisite for developing a strategy of management and technical measures to ensure environmental safety territories. To a large extent, this applies to the Odessa Industrial-and-Urban Agglomeration (next -Odessa agglomeration).…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring of pollution of all environment components , Odnorih et al, 2020, Sakalova et al, 2019 is the basis for the assessment of environmental hazard degree and development of the strategies to minimize it. Regarding air pollution, it should be noted that the intensive growth in the number of road transport observed in Ukraine in the last decade contributes, on the one hand, to the economic development of the country, and on the other hand, is accompanied by a negative impact on urban ecosystems and human health.…”
Section: Introductionmentioning
confidence: 99%